Theater of acculturation : the Roman ghetto in the sixteenth century - Stow, Kenneth R. (University of Washington Press, 2001)
"Generations of tourists visiting Rome have ventured into the small section between the Tiber River and the Capitoline Hill whose narrow, dark streets lead to the charming Fountain of the Tortoises, the brooding mass of the Palazzo Cenci, and some of the best restaurants in the city. This was the site of the Ghetto, within whose walls the Jews of Rome were compelled to live from 1555 until 1870. In Theater of Acculturation, Kenneth Stow, leading authority on Italian Jews, probes Jewish life in Rome in the early years of the Ghetto."--Jacket